2003
DOI: 10.2466/pms.2003.97.3f.1150
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Type of Training Sport Practised on Psychological and Physiological Parameters during Exhausting Endurance Exercises

Abstract: The present purpose was to study the influence of the type of training sport practised (long distance running, sprinting, handball) on ratings of perceived exertion (RPE), estimation of time limit (ETL), and heart rate (HR) on running tests. It was hypothesised that these parameters would be related to the type of training sport practised. 31 trained women (10 endurance-trained runners, 10 sprinters, and 11 handball players) performed two exercises to exhaustion on an outdoor track. The first test was a graded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
3
4
0
1
Order By: Relevance
“…Training specificity is a well-known phenomenon in nondisabled individuals [38][39][40]. This study extends the literature by providing evidence of training specificity for chronic stroke survivors with persistent upper-limb motor deficits according to functional task components.…”
Section: Training Specificitysupporting
confidence: 70%
“…Training specificity is a well-known phenomenon in nondisabled individuals [38][39][40]. This study extends the literature by providing evidence of training specificity for chronic stroke survivors with persistent upper-limb motor deficits according to functional task components.…”
Section: Training Specificitysupporting
confidence: 70%
“…Triathletes were probably more accustomed with time to exhaustion particularly during cycling trials. Some studies have already shown that RPE and/or ETL may be related to the type of training sport practiced during exhausting endurance exercise showing that RPE was lower for running than cycling (Thomas et al 1995) or that RPE and ETL values were lower for runners than handball players and sprinters for a same relative maximal aerobic speed (Garcin et al 2003). However, this result could be likely in part related to sport-specificity of the cycle exercise used for testing.…”
Section: Prescription Congruencementioning
confidence: 99%
“…These scales are complementary tools because the RPE scale is concerned with the current status of the subject (how hard he/she feels the exercise currently is) whereas the ETL scale deals with a subjective prediction of how long the current exercise intensity can be maintained. The concurrent validity of the ETL scale has been studied through the HR (Garcin et al 1999) and exercise relative intensity in various populations (Garcin et al 1999(Garcin et al , 2003(Garcin et al , 2004Garcin and Billat 2001). Moreover, the reliability of the ETL scale has been established during incremental and constant velocity runs in physical education students (Garcin et al 2003) and during field tests in trained male runners (Coquart and Garcin 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type of sport (sprinting and handball) contributes significantly to Estimated Time Limit response at the velocity corresponding to the lactate concentration threshold (partial R2 equal to 6%). Garcin, Mille-Hamard, Devillers, Dufour, Delattre, and Billat (2003) have already shown that Rating of Perceived Exertion and Estimated Time Limit were influenced by the type of training sport practised. As suggested by these authors, it seems these results are due to the sport-specificity of the exercise modes used for testing, i.e., this test remains specific for running.…”
Section: Discussionmentioning
confidence: 95%